Natural hazards - Edward Bryant (Cambridge Univ. Press, 1991)
The book describes and explains the natural hazards, examines prediction methods, considers recent and historical case-studies of notables hazard events and explores the social impact of such disasters. *) Climatic hazards include: tropical cyclones, tornadoes, large storms and winds; oceanographic hazards such as waves, sea-ice, sea level rise and beach erosion; drought, flood, hail, lightning snow and bushfires. *) Geographical hazards include: earthquakes and volcanoes, and associated events auch as tsunami, lava flows and atmospheric effects; and land instability